A TALE OF TWO MOLECULAR CALIFORNIAS - Jabloner, Anna (Science as culture, 2019)
Molecular identification technologies are often framed in terms of their societal benefits. Forensic uses of DNA databases benefit society through the efficient identification of criminal suspects, while consumer DNA services empower individuals by identifying ethnic, health-related, and potentially sexual, molecular genealogies. Two examples of these technologies are California's criminological database CAL-DNA and the revitalized project to find a 'gay gene'. Both examples show how molecular identification technologies are also entangled with histories of coercion and stigmatization. The search for a 'gay gene' is premised on the historical stigmatization of homosexuality as deviant as well as contemporary concerns with resisting the idea that it is a lifestyle choice. The CAL-DNA database demonstrates that stigmatization still underpins contemporary identification technologies. This 'race-neutral' database puts racial minorities at increased risk of getting caught up in the criminal system precisely because of a racist history of identifying men of color as potential criminals. While the increasing criminological and consumer applications of molecular identification technologies are spearheaded in California, their uses emerge in a futurist culture that decontextualizes them from historic and contemporary coercion. The molecular identities these technologies create tell a tale of two Californias; one of empowerment and another of surveillance and stigma